Clinical evaluation of healing of mandibular parasymphysis fractures with teeth in the fracture line (Update Dental College Journal, 2017)
Introduction: The aim of this study was to evaluate the postoperative results of mandibular parasymphysis fracture containing tooth in the fracture line.Materials and methods: The study was conducted at department of Oral & Maxillofacial Surgery, Dhaka Dental College and hospital. A total of 20 Patients included as study population, who were divided into two groups. Group I (retained group) consisted of 10 patients (50%) in which the teeth were retained in the fracture line. Group II (Extracted group) consisted of 10 patients (50%) in which teeth were extracted following specific criteria. All Patients were treated by open reduction and fixation with stainless steel miniplate and monocortical screw. Patients were followed up at 1st week, 8th week,12th week and 24th week of postoperative period and evaluated for healing related complications of fracture like infection, delayed union, malunion, and nonunion.Results: Out of 20 cases 3 patients (15%) had developed complications. In the retained group only one complication developed which was malunion. Where as in the extracted group two complications developed, one was delayed union and another one was infection. Postoperative complications rate in retained group was 10% and in extracted group it was 20%. In the early postoperative period the frequency of infection was more in both group and was decreased gradually with passage of time. In the 1st week of postoperative period the infection rate in extracted group was 20%. On the other hand in retained group it was 10%. No case of infection was found at following 8th and 12th week. After 24th week, 10% infection rate was found in extracted group and it was 0% in retained group. 10% delayed union was found in extracted group but absent in retained group. No case of malunion was found in extracted group but it was 10% in retained group. The complications rates were lesser in retained group than extracted group.Conclusion: Teeth associated with mandibular parasymphysis fracture should not be removed on a prophylactic basis to reduce the risk of complications of fractures site without an absolute indication for removal.Update Dent. Coll. j: 2016; 6 (2): 06-12